Role of an onsite healthcare programme in ocular diseases among construction workers: Observations from a health facility in Gujarat - Mamta Singh; Bibhuti P. Sinha; Rima B. Shah; Siddhartha Dutta (Journal of Family Medicine and Primary Care)
Background: Gujarat Building and Other Construction Labor Welfare Board started the Dhanvantari Arogya Rath Yojana (mobile vans equipped with healthcare facility) in 2015 to provide basic health services to construction workers and their families at their doorsteps. Objective: to evaluate the impact of an onsite healthcare programme on the management of eye diseases among construction workers. Method: retrospective analysis of case records of patients who visited the eye outpatient department between 1 January 2022 and 31 December 2022, having initially sought assistance from the onsite mobile healthcare services. The demographic and relevant clinical details were recorded. The clinical diagnosis at the time of examination and further management provided in outpatient department (OPD) for these cases, were documented. Result: A total of 55 clinical records of construction works were included in this study with mean age of 29.4 ± 10.02 years. The mean time of presentation to OPD was 72 ± 11 hours. 63.6% of these patients had corneal foreign body (FB), 20% of them had refractive error, 12.7% had conjunctivitis, 1.8% had anterior uveitis and another 1.8% had chemical injury to eye. None of them were wearing protective gear at the time of injury. 60% of them had evidence of previous ocular injuries. The mean presentation time for corneal FB patients was 94 ± 18 hours, and two of them had surrounding infiltration. Patients with conjunctivitis were symptomatically better with the given treatment. Conclusion: Onsite healthcare programme plays an important role in few ocular diseases. By incorporation education on prevention of ocular injuries, ocular hygiene, by training its members in basic ophthalmic techniques and ophthalmic emergency management, and developing a customized module depending on risk level of ongoing work can enhance its utility multiple folds.